Sex Differences in the Adult Human Brain: Evidence from 5216 UK Biobank Participants. (16th May 2018) - Ritchie, Stuart J; Cox, Simon R; Shen, Xueyi; Lombardo, Michael V; Reus, Lianne M; Alloza, Clara; Harris, Mathew A; Alderson, Helen L; Hunter, Stuart; Neilson, Emma; Liewald, David C M; Auyeung, Bonnie; et al.
Abstract: Sex differences in the human brain are of interest for many reasons: for example, there are sex differences in the observed prevalence of psychiatric disorders and in some psychological traits that brain differences might help to explain. We report the largest single-sample study of structural and functional sex differences in the human brain (2750 female, 2466 male participants; mean age 61.7 years, range 44–77 years). Males had higher raw volumes, raw surface areas, and white matter fractional anisotropy; females had higher raw cortical thickness and higher white matter tract complexity. There was considerable distributional overlap between the sexes. Subregional differences were not fully attributable to differences in total volume, total surface area, mean cortical thickness, or height. There was generally greater male variance across the raw structural measures. Functional connectome organization showed stronger connectivity for males in unimodal sensorimotor cortices, and stronger connectivity for females in the default mode network. This large-scale study provides a foundation for attempts to understand the causes and consequences of sex differences in adult brain structure and function.